Determinants Of Repayment Behaviour In Islamic Microfinancing: The Case Of Rural Economy Funding Scheme - Abu Hassan, Mohamad Hanif (2021)
This study attempted to identify the determinant of repayment behaviour from Islamic microfinance programmes in Malaysia. Based on theory of reinforcement which was supported by the theory of behaviour and asymmetric information theory, as well as past related studies, 5 hypotheses were established in this study. The results of the analysis showed that borrowers’ repayment behaviour were affected by their characteristics and accountability. Moreover, religiosity and business performance did not have a significant direct relationship with repayment behaviour. This research also found that accountability played a significant positive role as a mediator between borrower characteristic (financial strength, religiosity, understanding contract, and business performance) and repayment behaviour.